Saddle‐shaped rotating knee prosthesis outperforms low contact stress knee: A short‐term retrospective comparative study - Masafumi Itoh; Junya Itou; Umito Kuwashima; Ken Okazaki (Journal of Experimental Orthopaedics)
Abstract Purpose This retrospective comparative study aimed to compare the native patellar alignment and clinical outcomes of the Rotating Concave–Convex (ROCC) knee, which features a saddle‐shaped rotating platform (RP) insert and a deep trochlea, versus the low contact stress (LCS) knee, which has favourable long‐term outcomes and features an anatomically shaped trochlea and a cruciate‐sacrificing RP insert. We hypothesized that the deeper trochlea of the ROCC would further stabilize the native patella, resulting in superior clinical outcomes compared to LCS‐RP. Methods Consecutive patients who underwent patellar‐nonresurfacing primary total knee arthroplasty (TKA) using ROCC or LCS‐RP were retrospectively reviewed. Patients with over 1‐year post‐TKA follow‐up were included. Patients with neurologic disorders affecting knee function or additional ipsilateral knee surgery before evaluation were excluded. Patellar alignment was evaluated using the patella tilting angle (PTA), patella shift (PS), and the ratio of patella fitting depth into the trochlea (F) on axial radiographs. Primary and secondary outcomes were evaluated using the patellar score assessing patellofemoral function and Knee Injury and Osteoarthritis Outcome Score. Multiple regression analyses were performed with primary and secondary outcomes as dependent variables. Results The analysis included 113 ROCC knees and 94 LCS‐RP knees (median follow‐up: 25 months, follow‐up rate: 92.3%). For ROCC and LCS‐RP, respectively, the mean PTA was 0.3 (3.2)° and 4.3 (2.9)°; PS was 0.5 (1.8) and 2.0 (2.5) mm; and F was 29.6 (8.1)% and 21.4 (6.5)% (all p < 0.001). On multivariate analysis, ROCC positively affected both primary and secondary outcomes (p = 0.004 and 0.0003–0.02, respectively). Conclusion At short‐term follow‐up, ROCC stabilized the patella further horizontally, centrally, and deeply into the trochlea, thus outperforming LCS‐RP clinically. Orthopaedic surgeons should consider these potential advantages when selecting TKA models, especially those featuring cruciate‐sacrificing RP mechanisms in patellar‐nonresurfacing procedures. Level of Evidence III. Retrospective comparative study.